TECHNIQUES FOR ASSESSING THE INVESTMENT ATTRACTIVENESS OF A COMMERCIAL ORGANIZATION BASED ON CLASSICAL METHODS OF STRATEGIC ECONOMIC ANALYSIS - Olimov , Iskandar Salimboyevich; Karimov , Abdukodir Abdisalomovich (Innovative Development in Educational Activities, 2023)
The development of methodological support for assessing the investment attractiveness of a commercial organization, considering modern information requests of stakeholders. As part of the research, the authors have developed an algorithm for investment attractiveness assessment of a commercial organization by using the scenario method of economic analysis.It is proved that the main disadvantages of the existing methods of assessing investment attractiveness are: the lack of strategic orientation of the assessment; ignoring the influence of most external and internal factors of activity; the inability to assess the risk of investing in the analyzed object; the need to compare with the level of investment attractiveness of similar organizations for an objective interpretation of the results. To eliminate the significant shortcomings of modern methodological support in this area, the authors recommend the use of scenario method of strategic economic analysis in the process of assessing the investment attractiveness of the organization.